Evaluation of Increasing Trypsin Inhibitor on Nursery Pig Growth Performance, Fecal Dry Matter, and Nutrient Digestibility - Sierra M. Collier; Paige T. Soper; Katelyn N. Gaffield; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Hari B. Krishnan; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 360 barrows (DNA 200 × 400; initially 13.4 ± 0.07 lb) were used in a 42-d growth trial to evaluate the effects of increasing trypsin inhibitor on nursery pig growth performance. At weaning, pigs were randomly assigned to pens with five pigs per pen and 12 pens per treatment. There were six dietary treatments formulated to provide 1.4, 2.1, 2.8, 3.5, 4.2, and 4.9 trypsin inhibitor units (TIU)/mg of complete feed. Soy flour (76 TIU/mg) was added at the expense of soybean meal (5 TIU/mg) to create the treatment TIU levels. Diet formulation was based on analyzed nutrient values of the soy flour and soybean meal but assumed the same digestibility coefficients for each, which matched that of the soybean meal. Experimental diets were fed in three phases: phase 1 from d 0 to 10, phase 2 from d 10 to 24, and phase 3 from d 24 to 42. Across all three individual dietary phases and overall (d 0 to 42), increasing TIU decreased (linear, P < 0.001) ADG and ADFI and worsened (linear, P < 0.001) F/G. Fecal DM on d 10 increased (linear, P < 0.05; quadratic, P = 0.088) as TIU increased, with the majority of increase in fecal DM tending to be from 3.5 to 4.9 TIU/mg of complete feed. However, there were no differences in fecal DM on d 42. The apparent total tract digestibility (ATTD) of DM decreased then increased (linear, P = 0.001; quadratic, P = 0.003) as TIU increased in the diet, with the lowest ATTD of DM occurring at 4.2 TIU/mg of complete feed. Furthermore, the ATTD of CP decreased (linear, P < 0.001) as the level of TIU/mg of complete feed increased in the diet. In conclusion, these data suggest that increasing dietary TIU above 1.4 TIU/mg of complete feed results in poorer nursery pig growth performance and reduced ATTD of nutrients, although feces were drier on d 10 but not at the end of the study.
Keywords: soybean meal; trypsin inhibitor; weanling pigs